1975
DOI: 10.1136/bmj.3.5975.73
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic fluoride treatment and aged bones.

Abstract: BRITISH MEDICAL JOURNAL12 JULY 1975 7. that CO could be implicated in any of the health improvements attributable to smoking cigarettes with unventilated filter-tips. Unfortunately, hopes that tobacco subsitutes may be safer to smoke have not as yet been supported, at least so far as CO production is concerned. Planet cigarettes, which were hastily withdrawn just over a year ago, had a CO yield well above the other brands used in this study. It was also higher than has ever been reported for cigarettes. Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 10 publications
(2 reference statements)
0
15
0
Order By: Relevance
“…They suggested that although fluoride stimulates new bone formation, the absence of adequate available calcium probably resuits in the formation of poorly calcified matrix, in effect, osteomalacia. Inkovaara et al [19], in a prospective trial in osteoporotic patients, noted an increase in vertebral fractures in those receiving fluoride.…”
Section: Discussionmentioning
confidence: 97%
“…They suggested that although fluoride stimulates new bone formation, the absence of adequate available calcium probably resuits in the formation of poorly calcified matrix, in effect, osteomalacia. Inkovaara et al [19], in a prospective trial in osteoporotic patients, noted an increase in vertebral fractures in those receiving fluoride.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that NaF could lead to a decrease in cortical bone mass especially in the distal radius [1, 3,10,13]. Some authors [3,[23][24][25], have even reported a higher incidence of non-spine fractures (especially hip fractures). However, analysis of the results reveals that these hip fractures usually occurred in older patients over 70, often in a bone fluorosis context [23], probably related to the combination of higher doses used, or too lengthy a period of treatment often without coadministration of calcium supplement, or renal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge they have not been described in steroid-induced osteoporosis treated with fluoride. Similarly, although femoral neck fractures have been reported [4,9,10,12,18], trabecular fatigue fractures in the femoral head have never been noted during fluoride therapy. In our case, the groin pain was related to an unusual supraacetabular fracture, followed by same sided femoral head trabecular fractures.…”
Section: Discussionmentioning
confidence: 99%